Two-stage anaerobic digestion system treating different seasonal fruit pulp wastes: Impact on biogas and hydrogen production and total energy recovery potential. (October 2020) - Mateus, Sara; Carvalheira, Mónica; Cassidy, Joana; Freitas, Elisabete; Oehmen, Adrian; Reis, Maria A.M.
Abstract: Anaerobic digestion has been shown to be an effective treatment for high organic matter wastes, while producing clean energy. However, anaerobic digesters in some companies must support variations of substrate composition due to the seasonality of feedstocks. In this study, a two-stage anaerobic digestion system was operated treating three different fruit pulp wastes in a sequential operation. The effect of substrate shifts and operational conditions on acidogenesis, biogas production/composition and overall system performance was assessed. Substrate shifts did not cause long-term instability issues. No evident association was found between operational condition changes on the profile of fermentation products and acidification degrees (53.7%–76.4%) in the acidogenic stage. However, substrate composition affected the gas production in the acidogenic stage, whereas it had no effect on the gas production in the methanogenic stage. The initial substrate composition affected the percentage of hydrogen (H2 ) (0–34%) in the biogas produced in the first stage. Consistently high methane (CH4 ) yields (0.30–0.37 LCH4 g −1 CODdegraded ) were obtained in the methanogenic stage. The biogas produced in the second stage (0.5–2.1 LCH4 L −1 d −1 ) was rich in CH4 (75.9–80.6%) regardless of the operational conditions tested. The CH4 produced could be used to generate energy up to 79.5 kJ Lreactor −1 d −1 while the H2 production in the acidogenic reactor, when treating fruit pulp waste with high content of sugars, could further increase this energy by up to 22.4% (H2 content between 25 and 30%). This process has shown to be robust in treating seasonal wastes from a fruit juice industry, supporting full scale application. Highlights: Seasonal fruit pulp wastes were sequentially treated and converted into biogas. Operational conditions changes did not affect the performance in terms of COD removal. H2 production was affected by different substrates, mainly due to the sugar content. High CH4 productivity (up to 2.13 L L −1  d −1 ) and yield were consistently achieved. Potential energy generation from H2 and CH4 up to 97.24 kJ Lreactor −1 d −1 .